KAJIAN HISTORISITAS ILMU BALAGAH DAN PENGARUHNYA TERHADAP PERKEMBANGAN CORAK TAFSIR - Muhammad Patri Arifin (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2023)
This article examines the historical development of balāghah (Arabic rhetoric) and its influence on the evolution of Qur’anic exegesis (tafsir). The balāghī approach to interpretation focuses not only on the lexical meanings of Qur’anic verses but also on their deeper and implicit meanings through the study of al-Bayān, al-Ma‘ānī, and al-Badī‘. The emergence of this interpretive style was closely linked to the development of Arabic literature and rhetoric, both before and after the advent of Islam. Following the revelation of the Qur’an, the study of balāghah flourished as scholars and literary critics became increasingly interested in the linguistic beauty and rhetorical excellence of the Qur’an. This intellectual development gave rise to important works in Qur’anic rhetoric and exegesis, including Majāz al-Qur’ān by Abu Ubaydah, Dalā’il al-I‘jāz by Abd al-Qahir al-Jurjani, and al-Kashshāf by al-Zamakhshari. The study concludes that the science of balāghah played a significant role in shaping the balāghī tradition of Qur’anic interpretation.